2023
DOI: 10.1111/obr.13555
|View full text |Cite
|
Sign up to set email alerts
|

Double‐ and triple‐duty actions in childhood for addressing the global syndemic of obesity, undernutrition, and climate change: A scoping review

Abstract: Summary Obesity, undernutrition, and climate change constitute a global syndemic that disproportionately affects vulnerable populations, including children. Double‐ and triple‐duty actions that simultaneously address these pandemics are needed to prevent further health, economic, and environmental consequences. Evidence describing the implementation and evaluation of such actions is lacking. This review summarized the literature on whole‐of‐population actions targeting children that were designed or adapted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…The measurement of menu compliance alongside food waste ensured that we were able to consider both healthfulness and environmental sustainability of the food provided. Finally, our research sets the stage for future triple-duty action research and interventions in childcare settings, which has been found to be more effective than addressing each component in isolation ( 44 ) .…”
Section: Discussionmentioning
confidence: 95%
“…The measurement of menu compliance alongside food waste ensured that we were able to consider both healthfulness and environmental sustainability of the food provided. Finally, our research sets the stage for future triple-duty action research and interventions in childcare settings, which has been found to be more effective than addressing each component in isolation ( 44 ) .…”
Section: Discussionmentioning
confidence: 95%
“…For adequacy components, consumption equal to or above the recommended percentage of total energy intake is given the highest score while consumption below the recommended percentage of total energy intake is given proportionally lower scores; for ratio and optimum components, consumption equal to or close to the recommended percentage of total energy intake is given higher scores while consumption either above or below the recommended percentage of total energy intake is given proportionally lower scores; lastly, for moderation components, consumption equal to or close to zero is given higher scores while consumption above zero is given proportionally lower scores. Of note is that consumptions outside the recommended range of percentage of total energy intake for each component are given zero points based on sustainable healthy dietary guidelines [35] along with policies limiting access and exposure to unhealthy food and beverages [2], can help achieve this goal. In Chile, the introduction of the Food Labelling and Advertising Law at the end of June 2016 [36] may have reduced children's intake of added sugars and saturated fats from ultra-processed products consumed at schools [37]; however, it is still unknown whether this policy has improved their adherence to sustainable healthy diets.…”
Section: Discussionmentioning
confidence: 99%
“…This approach should incorporate triple-duty actions, considering the distinctive aspects of diverse life stages. [41].…”
Section: Discussionmentioning
confidence: 99%